Sustaining adaptive collaborative management processes: Challenges and opportunities from Mafungautsi State Forest, Gokwe, Zimbabwe - Witness, K.; Nyirenda, R.; Mutimukuru-Maravanyika, T.; Matose, F.; Ngwenya, M.; Sibanda, L. (Routledge, 2023)
An adaptive collaborative management (ACM) project was implemented in Mafungautsi State Forest, in the Gokwe South District of Zimbabwe between 1999 and 2006. By 2005, significant collaborative momentum between local resource users and officialdom at various levels had been created. Over the same period, Zimbabwe experienced unprecedented changes associated with its land reforms, profoundly impacting natural resource management. State forests became frontiers for contestation for land and forestry resources between the state and land-hungry, internal migrants and those displaced when the forests were reserved. This chapter examines the earlier ACM processes against the backdrop of this national meltdown. Interviews and desk study yielded longitudinal data that tracked nuances in the dynamics and endurance of ACM processes. The study provides important insights that can enhance ACM efficacy and functionality under a unique ‘test’ environment characterized by severe economic and socio-political stress, lessons presumably also applicable under more normal conditions. Despite these political economic factors that had a profound impact on local ACM processes, residual elements of ACM remained around Mafungautsi. Forestry Commission (FC) management still considers ACM a policy option, albeit in largely rhetorical terms. We conclude that ACM can contribute to dealing with the complex situations faced in this forest and elsewhere.